FISH for EWSR1 in Ewing's sarcoma family of tumors: Experience from a tertiary care cancer center - Sudha S Murthy; Sandhya Devi Gundimeda; Sundaram Challa; V Manjula; Daphne Fonseca; Vishal B Rao; Senthil J Rajappa; K V. V N Raju; T Subramanyeshwar Rao (Wolters Kluwer Medknow Publications, 2021)
Background: Molecular confirmation of histologic diagnosis has become mandatory for the diagnosis of Ewing sarcoma family of tumors (ESFT). Aim: To validate the diagnosis made by morphology and immunohistochemistry (IHC) by fluorescence in-situ hybridization (FISH) for EWSR1 rearrangement on formalin fixed paraffin embedded (FFPE) tissues. Settings and design: A retrospective and prospective observational study. Material and methods: All patients who had FISH studies for EWSR1 rearrangement for small round cell tumors during 10 years period were included. Demographic, clinical and radiological details were obtained from medical records. Morphology was reviewed with IHC by CD99, FLI1 and others. FISH studies were performed using the break apart probe. Additional molecular studies and IHC were done to resolve the diagnosis in EWSR1 rearranged tumors. Final diagnosis was made by integrating clinical, morphology, IHC and molecular features. Results: There were 81 patients (M: F 45:36, median age 21 years) with 32 skeletal and 49 extra skeletal tumors. CD 99 was positive in 94.52%. FISH for EWSR1 were positive in 59, negative in 13 and failed in 9. The final diagnosis was made as ESFT in 67, angiomatoid fibrous histiocytoma in 3, desmoplastic small round cell tumor in 3, myxoid chondrosarcoma in 2, unclassified in one, synovial sarcoma in 3, and one each of lymphoma and small cell neuroendocrine carcinoma. FISH was positive for ESFT in 89.83% of EWSR1 rearranged tumors. FISH validated the diagnosis made on IHC in 79.10%. FISH resolved the diagnosis in 1.49% CD99 negative tumors. Conclusion: FISH is a reliable ancillary technique for the diagnosis of ESFT on FFPE tissues.